Patients' Perspectives of Fast-Track Surgery and the Role of the Fast-Track Clinical Nurse Consultant in Gynecological Oncology. Issue 3 (May 2015) - Philp, Shannon; Carter, J.; Barnett, C.; D'Abrew, N.; Pather, S.; White, K.
Abstract : This study examines the role of the fast-track nurse in gynecology from a patient perspective. The fast-track nurse is a specialist nursing role, which coordinates patient care, in addition to providing specialized clinical care. Semistructured interviews were conducted with women who had fast-track surgery for gynecological cancer.